2020
DOI: 10.1140/epjc/s10052-020-08645-w
|View full text |Cite
|
Sign up to set email alerts
|

Holographic Lifshitz superconductors with Weyl correction

Abstract: At the probe approximation, we construct a holographic p-wave conductor/superconductor model in the five-dimensional Lifshitz black hole with the Weyl correction via both numerical and analytical methods, and study the effects of the Lifshitz parameter z as well as the Weyl parameter $$\gamma $$ γ on the superconductor model. As we take into account one of the two corrections separately, the increasing z ($$\gamma $$ γ ) inhibits(enhances) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 57 publications
1
9
0
Order By: Relevance
“…. Compared with the scaling dimension Δ ± in [58][59][60], here, Δ ± depends on both Lifshitz and Weyl parameters and thus suggests that the present model might display more interesting features. From the holographic dictionary, ψ 1 and ψ 2 are usually explained as the source and the vacuum expectation values of the dual operator Ĵx , respectively, while μ and ρ are respectively regarded as the chemical potential and the charge density of boundary field theory.…”
mentioning
confidence: 77%
See 3 more Smart Citations
“…. Compared with the scaling dimension Δ ± in [58][59][60], here, Δ ± depends on both Lifshitz and Weyl parameters and thus suggests that the present model might display more interesting features. From the holographic dictionary, ψ 1 and ψ 2 are usually explained as the source and the vacuum expectation values of the dual operator Ĵx , respectively, while μ and ρ are respectively regarded as the chemical potential and the charge density of boundary field theory.…”
mentioning
confidence: 77%
“…What is more, at the low temperature ( ) . Comparing the effects of the new Weyl coupling, CB 2 , with the one of the previous Weyl couplings, CF 2 , on the vector condensate, we find that the effect of the new coupling, CB 2 , is weaker than that of the old Weyl coupling CF 2 , [60] based on the left panel in figure 1. Furthermore, when γ = 0, the present model is the same as the one in [60] with a vanishing CF 2 correction and the model in [42] without an RF 2 correction.…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…In Ref. [11], the author performed a 3 P 0 model analysis which contain strong decay behaviors and suggested that the Ξ c (2923) 0 and Ξ c (2938) 0 might be 1P Ξ c states and Ξ c (2965) 0 can be 2S Ξ c states. In addition, lattice simulations also investigated these heavy flavored baryons [12][13][14].…”
Section: Introductionmentioning
confidence: 99%